Studies on Understanding and Using Sino-Vietnamese Words Among High School Students in Southeast Vietnam - Hoang, Quoc (Technium Social Sciences Journal, 2024)
Sino-Vietnamese words make up a significant portion of the Vietnamese language—over 60%—and play a crucial role in its vocabulary. However, understanding and effectively using Sino-Vietnamese words can be challenging due to their complexity. This difficulty is especially pronounced for students, often leading to misunderstandings, incorrect word usage (in both speaking and writing), and overreliance on these terms. Many students lack awareness of the role language plays in communication and in studying Literature, resulting in a detached attitude toward the subject, with some even taking it lightly in school. Additionally, teaching methods and teacher expertise influence the quality of Literature education, particularly regarding Sino-Vietnamese vocabulary. This study surveyed 600 tenth-grade students from eight high schools across four provinces and cities in Southeast Vietnam. A combination of questionnaires, observations, and in-depth interviews was used to gather data. Based on the findings, this research highlights the current state of students’ comprehension and use of Sino-Vietnamese words and proposes practical solutions to improve the teaching and learning of Vietnamese language and literature, with a special focus on Sino-Vietnamese vocabulary.